ANALISIS PENGARUH CORPORATE GOVERNANCE, AUDIT, DAN MANAJEMEN BIAYA TERHADAP DAYA SAING EKONOMI PERUSAHAAN PADA PERUSAHAAN TRANSPORTASI YANG TERDAFTAR DI BURSA EFEK PERIODE 2022-2024 - Sitinjak, Putri Rejeki; Sinaga, Klara Hotmauli; Hutagaol, Erika Damayanti; Sipahutar, Tetty Tiurma Uli; Manurung, Ria (POLITEKNIK LP3I JAKARTA, 2026)
This study uses data from transportation sector companies listed on the Indonesia Stock Exchange for the 2022–2024 period to analyze the effect of corporate governance, audit, and cost management on economic competitiveness, measured by Return on Assets (ROA). The study applies a quantitative approach using multiple linear regression with a sample of 24 companies and 72 observations. The results show that corporate governance has no significant effect, indicating that its implementation is still formal. Audit has a positive and significant effect, suggesting that audit improves transparency and trust. Cost management has a significant negative effect, indicating that inefficient cost management reduces competitiveness. Simultaneously, all variables have a significant effect with a coefficient of determination of 23.1%, meaning part of competitiveness is explained by the model while the rest is influenced by other factors. This study highlights the importance of audit quality and cost efficiency, as well as the need to optimize corporate governance